PENGARUH KOMITMEN DAN ETOS KERJA TERHADAP RODUKTIVITAS KERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN SITUBONDO - Ika Wahyuni; Rita Wardatul Ulum (Relawan Jurnal Indonesia, 2018)
The purpose of this research is (1) to know the influence of commitment and work ethic partially and simultaneously to work productivity of employee at Badan Peanggulangan Bencana Daerah Kabupaten Situbondo (2) to know among the most dominant commitment and work ethic variable influencing the work productivity of employees at Badan Penanggulagan Bencana Daerah Kabupaten Situbondo. Population of the research as many as 32 employees and the sample used 32 employees using saturated sample technique. The method used in this research is quantitative method. The result of research is multiple linear regression equation Y = 7,722E-18 + 0,503X1 + 0,470X2 + e. The partial commitment has a significant positive effect with the value of tcount of 3,523, ttable of 2.045, and work ethos have a significant positive effect with the value of tcount 3.293, ttable of 2.045. Simultaneously commitment and work ethic have an effect on work productivity with value Fcount equal to 10,389, Ftable equal to 3,33. The most influential variable dominant in this research is commitment with value equal to 3,523